A New Composite General Iterative Scheme for Nonexpansive Semigroups in Banach Spaces - Pongsakorn Sunthrayuth; Poom Kumam (International Journal of Mathematics and Mathematical Sciences)
We introduce a new general composite iterative scheme for finding a common fixed point of nonexpansive semigroups in the framework of Banach spaces which admit a weakly continuous duality mapping. A strong convergence theorem of the purposed iterative approximation method is established under some certain control conditions. Our results improve and extend announced by many others.